309 Sonograhic Appearances of Hobnail Thyroid Carcinoma: A Rare Tumour. (19th August 2022) - Karunaratne, Nisal; Kirkland, Paul; Zhang, Ting Ting; Shiekh Ali, Zainab Al; Howlett, David
Abstract: Background: Hobnail papillary thyroid carcinoma is a rare, recently described papillary thyroid carcinoma variant, with potential for a more aggressive clinical course of disease and poorer prognosis1. The ultrasound features of papillary thyroid carcinoma variants can differ from known traditional features1 and the specific sonographic findings of the hobnail variant itself have not been previously described in the literature. Case report: A 53-year-old man presented with a left thyroid mass. The ultrasound features of this mass included a predominantly cystic appearance with mobile internal echoes, vascularised internal septations, and murally based solid material. These ultrasound features were deemed benign by classification standards, which led to the patient being managed with active surveillance and interval imaging. However, the mass grew quickly, and the patient underwent diagnostic hemithyroidectomy which led to hobnail variant papillary thyroid carcinoma being found on pathology. Given that papillary thyroid carcinoma variants can lead to aggressive disease, the patient underwent completion thyroidectomy and level VI lymph node clearance, on multidisciplinary team recommendation. Discussion: The ultrasound features of the hobnail variant of papillary thyroid carcinoma have not been previously described in detail in the literature and, in this case, are features that would be deemed benign by classification standards. The rapid growth of the mass is what led to clinical suspicion of malignancy and resulted in diagnosis. Therefore, careful clinical correlation is advised in order to discern this difficult diagnosis and to facilitate appropriate treatment.